Study on mixing interface of continuous large drop and U-shaped product pipeline - Feng Liang (E3S Web of Conferences, 2021)
In the long-distance pipeline of product oil, gasoline and diesel oil are transported in batches. Due to the large difference of physical properties between the two kinds of oil products, there will be oil mixing at each interface. Because the index parameters of mixed oil do not meet the sales standard, it is necessary to track the interface accurately, so as to provide necessary reference for cutting mixed oil. The topography of southwest mountainous area is characterized by continuous large drop and U-shape, which brings difficulties to batch tracking of product oil pipeline. The previous method is not suitable for this type of pipeline. Therefore, it is necessary to re study the batch tracking method of this type of product pipeline, and use vs2019 to write batch tracking software for continuous large drop and U-shaped product pipeline based on this method. The batch tracking error of the software for this type of pipeline is within the acceptable range, which can provide more accurate reference for the operation control personnel